Effects of blood pressure on white matter lesions and brain volumes in hypertensive and normotensive subjects. (1st February 2022) - Woldstad, Christopher J; Rusinek, Henry; Sweeney, Elizabeth; Mardy, Christopher; Butler, Tracy; Li, Yi; Osorio, Ricardo S; Tanzi, Emily; Harvey, Patrick; de Leon, Mony J.; Glodzik, Lidia
Abstract: Background: There is a direct relationship between cardiovascular dysfunction and risk factors and the development of the diseased brain. Such an affiliation has been made clear by decades of comprehensive studies associating poor cardiovascular health with adverse neurological events such as stroke, brain atrophy, and dementia. Hypertension and its subsequent pathological hallmarks can ultimately lead to cognitive dysfunction such as Alzheimer's disease. Although benefits of hypertension (HTN) treatment are indisputable, the target blood pressure value remains under debate. Method: Our group performed a cross‐sectional (n = 376) and longitudinal (n = 188) study of subjects that were approximately 60% women (age 68.5 ± 7/4 years, mean age 70.7±6.9 years) without any clinically demonstrable signs of dementia or stroke. Subjects were split into hypertensive (n = 169) and normotensive (n = 207) cohorts. MR images were obtained on a 3T system using fluid attenuation inversion recovery (FLAIR) and arterial spinal labeling (ASL) sequences. Linear modeling was performed in hypertensive and normotensive cohorts to investigate the relationship between blood pressure, white matter lesion (WML) development and hippocampal brain volume changes. Result: Subjects in the hypertensive cohort showed a quadratic relationship between systolic blood pressure and WML, with the lowest amounts of WML being measured in subjects with readings at approximately 124 mmHg. Additionally, the hypertensive cohort also exhibited a quadratic relationship between diastolic blood pressure and hippocampal brain volume; subjects with readings at approximately 79 mmHg showing the largest volumes. Longitudinally, among hypertensive individuals both baseline SBP (β= 0.34, p=0.01) and DBP (β= ‐0.29, p=0.03) were related to WML changes over time (entire model F2, 82 =3.9, p=0.024). Conclusion: While it is evident that higher blood pressure ultimately results in increased neuropathology across all subjects, it appears that in the hypertensive group there is a valley of mid‐range blood pressures displaying less pathology in the brain.